Arterial eicosanoid production following chronic exposure to a periarterial haematoma. Issue 7 (July 1984) - Pickard, J D; Walker, V; Perry, S; Smythe, P J; Eastwood, S; Hunt, R
Abstract : Cisternal and lumbar cerebrospinal fluid obtained some days following a subarachnoid haemorrhage contains abnormally large quantities of various prostanoids; some may be partly the result of abnormal production by the cerebral arteries. The extra-arterial and intra-arterial production of 6 oxo PGF1 alpha (prostacyclin metabolite), PGE2, PGF2 alpha and TXB2 were measured in perfused rabbit common carotid arteries taken both from normal rabbits and from rabbits in which the arteries had been ensheathed by blood clot in vivo for 7 days using two techniques. Prostaglandin production by control arteries was highest during the first hour of perfusion but declined or increased marginally (PGE2) during the succeeding three hours. Arteries exposed to a periarterial haematoma for 7 days produced prostaglandins at a high rate throughout the 4 hours of study, and there was a progressive and marked increase in PGE2 production. The disproportionate increase in the cerebral vasoconstrictor PGE2 may reflect the inflammatory response which occurred in the adventitia of the vessels. Increased prostanoid production by cerebral arteries probably does contribute to the increased levels in CSF after subarachnoid haemorrhage.